High diversity and low specificity of fungi associated with seedless epiphytic plants. (25th November 2022) - Cook, Kel; Taylor, D. Lee
Abstract: Epiphytes, which grow on other plants for support, make up a large portion of Earth's plant diversity. Like other plants, their surfaces and interiors are colonized by diverse assemblages of fungi that can benefit their hosts by increasing tolerance for abiotic stressors and resistance to disease or harm them as pathogens. Fungal communities associated with epiphytic plants and the processes that structure these communities are poorly known. To address this, we sampled seven epiphytic seedless plant taxa in a Costa Rican rainforest and examined the effects of host identity and microhabitat on external and endophytic fungal communities. We found low host specificity for both external and endophytic fungi and weak differentiation between epiphytic and neighboring epilithic plant hosts. High turnover in fungi within and between hosts and habitats reveals that epiphytic plant‐associated fungal communities are highly diverse and suggests that they are structured by stochastic processes. Abstract in Spanish is available with online material Abstract : Tropical forests can host a diverse assemblage of epiphytic plants, which in host communities of fungi. We assessed the host‐ and habitat‐specificity of epiphyte‐associated fungi, including endophytic fungi. We found small differences in fungal communities among hosts and habitat, suggesting that fungal communities are assembled largely through stochastic processes. RESUMO: Las epífitas, que crecen apoyándose en otras plantas, forman una gran parte de las varias plantas de la Tierra. Al igual que otras plantas, sus superficies e interiores están colonizados por diversos ensamblajes de hongos que pueden beneficiar a sus huéspedes al aumentar la tolerancia a factores estresantes abióticos y la resistencia a las enfermedades o dañarlos al actuar como patógenos. Las comunidades fúngicas asociadas a plantas epífitas y a los procesos que estructuran estas comunidades no son bien conocidas. Para examinar aquello, hemos recogido, en una selva tropical de Costa Rica, muestras de siete taxones de plantas epífitas sin semillas y hemos examinado los efectos de la identidad del huésped y del microhábitat sobre las comunidades fúngicas externas y endofíticas. Hemos encontrado una baja especificidad del huésped para ambos hongos externos y endófitos y una baja diferenciación entre las plantas huésped epífitas y sus vecinas epilíticas. La elevada rotación de hongos dentro y entre huéspedes y hábitats indica que las comunidades fúngicas asociadas a plantas epífitas son muy diversas y aquello sugiere que están estructuradas por procesos estocásticos.